THE INFLUENCE OF LOCAL GESTURE-BASED COMMUNICATION STYLES ON ENGLISH INTONATION MASTERY IN NON-VERBAL LEARNING ENVIRONMENTS (Modern education and development, 2025)
This study investigates how local gesture-based communication styles influence learners’ acquisition of English intonation in non-verbal learning environments. In multilingual and culturally rich regions, gestures and body language often serve as primary tools for expressing emotion, emphasis, and meaning. The research explores the extent to which these culturally ingrained non-verbal cues can enhance or hinder the mastery of English prosody, particularly intonation patterns. By examining classroom interactions, observational data, and learner reflections, the study highlights the role of embodied communication in shaping auditory language processing. Findings suggest that aligning English intonation instruction with learners’ native gestural frameworks can improve pronunciation, rhythm, and communicative clarity. This context-sensitive approach supports the development of intercultural competence and adaptive speaking strategies in English language education.